Evaluation of the seismic performance of an educational institution using nonlinear dynamic analysis - Ruiz-Pico, A. (2024)
Currently, there are a large number ofold educational institutions still in operation that were built without considering earthquake-resistant criteria. These buildings, being considered essential, must maintain their operability during and after a seismic event. In this research, two two-level modules with regular plans belonging to an educational institution built in 1994 were analyzed. These modules are characterized by having a reinforced concrete frame system in the X direction and a confined masonry system in the Y direction. These modules were analyzed by applying the linear parameters of NTP E.030 and nonlinear methodologies such as the Nonlinear Dynamic Analysis (NDA), where the structures were subjected to three seismic events that occurred in Peru, which were corrected, scaled, and matched to the response spectrum using Seismosignal and Seismomatch software. ETABS software was used for modeling andfollowing the guidelines of ASCE 41-17 and FEMA 356, the response of the seismic records in the north-south and east-west directions was evaluated, obtaining drifts and shear and displacement vs. time graphs. Based on the results, the seismic performance for both directions was obtained, considering the performance levels given by HAZUS99. It was determined that in the X direction, the performance is "Complete structural damage," and in the Y direction, it is "Slight structural damage," concluding that for this type of building, structural reinforcement in the X direction is necessary to improve performance.